Theory of a quantum artificial neuron based on superconducting devices - Katayama, Haruna; Fujii, Toshiyuki; Hatakenaka, Noriyuki (International Journal of Engineering and Technology, 2018)
An artificial neuron using superconducting devices, so-called rf SQUID, working at the quantum-mechanical domain is studied. It is shown that quantum rf SQUID regarded as flux qubit can act as an artificial neuron with sigmoid function generated by coherent quantum-mechanical transitions between wells in double well potential representing rf SQUID.Â Â Â